Isolasi Karakterisasi T Asam Humat dan Penentuan Daya Serap Nya Terhadap Ion Logam Pb(II) Cu(II) dan Fe(II) - Yati B Yuliyati; Christi Liamita Natanael (Study Program of Chemistry - Alauddin State Islamic University of Makassar, 2016)
Coal, which are decomposition resulted of natural biological processes over the years in which the humic acid compound contained. The purposes of this research was tocharacterize and to compare the humic acid of coal from South Borneo. The isolation of humic acid by leaching process uses natrium karbonat 0.1 N and fractionation uses sulfuric acid 6M. The fraction was purified and the deposit was washed by sulfuric acid 1 M, aquadest and ethanol. Moisture content, ash content, cation exchange capacity, C/N ratio and E4/E6ratiowithspectroscopy were characterized. The yields of humic acid areobtained 12.35% of coal. C/N ratio of humic acid 20.72. The infrared spectroscopy results of humic acid from coal figures more of aromatic and -OH group with lower E4/E6 ratio, while from peat soil shows more of aliphatic and carboxylic group supported higher E4/E6 ratio. Kapasitas tukar kation 640,59 mek/100g; dan mempunyai daya serap terhadap ion logam yang cukup baik.